Haste or Speed? Alterations in the Impact of Incentive Cues on Task Performance in Remitted and Depressed Patients With Bipolar Disorder - Chase, Henry W.; Fournier, Jay C.; Aslam, Haris; Stiffler, Richelle; Almeida, Jorge R.; Sahakian, Barbara J.; Phillips, Mary L. (Frontiers in Psychiatry, 2018)
A variety of evidence suggests that bipolar disorder is associated with disruptions of reward related processes, although the properties and scope of these changes are not well understood. In the present study, we aimed to address this question by examining performance of patients with bipolar disorder (30 depressed bipolar; 35 euthymic bipolar) on a motivated choice reaction time task. We compared performance with a group of healthy control individuals (n=44) and a group of patients with unipolar depression (n=41), who were matched on several demographic variables. The task consists of an ‘odd-one-out’ discrimination, in the presence of a cue signaling the probability of reward on a given trial (10%, 50% or 90%) given a sufficiently fast response. All groups showed similar reaction time (RT) performance, and similar shortening of RT following the presentation of a reward predictive cue. However, compared to healthy individuals, the euthymic bipolar group showed a relative increase in commission errors during the high reward compared to low condition. Further correlational analysis revealed that in the healthy control and unipolar depression groups, participants tended either to shorten RTs for the high rather than low reward cue a relatively large amount with an increase in error rate, or to shorten RTs to a lesser extent but without increasing errors to the same degree. By contrast, reward-related speeding and reward-related increase in errors were less well coupled in the bipolar groups, significantly so in the BPD group. These findings suggest that although RT performance on the present task is relatively well matched, there may be a specific failure of individuals with bipolar disorder to calibrate RT speed and accuracy in a strategic way in the presence of reward-related stimuli.